2014
DOI: 10.4081/aiua.2014.4.257
|View full text |Cite
|
Sign up to set email alerts
|

Urolithiasis in renal transplantation: Diagnosis and management

Abstract: Obiectives: To report our experience of diagnosis and multimodal management of urolithiasis in renal transplantation. Patients and Methods: From January 1995 to December 2012, 953 patients underwent renal transplantation in the Kidney Transplant Unit of Treviso General Hospital. Ten (10%) of them developed urinary calculi and were referred at our institution. Their mode of presentation, investigation and treatment were recorded. Results: Seven had renal and 3 ureteral calculi. Urolithiasis was incidentally dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 16 publications
0
9
0
1
Order By: Relevance
“…The remaining 157 articles underwent full-length review, and an additional 136 were excluded for failing to meet the criteria. Twenty one articles[12-29,36,38,40] met all inclusion criteria and were identified for the meta-analysis of kidney stones in kidney transplant recipients (Table 1). Supplementary Item 2 outlines our search methodology and selection process.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The remaining 157 articles underwent full-length review, and an additional 136 were excluded for failing to meet the criteria. Twenty one articles[12-29,36,38,40] met all inclusion criteria and were identified for the meta-analysis of kidney stones in kidney transplant recipients (Table 1). Supplementary Item 2 outlines our search methodology and selection process.…”
Section: Resultsmentioning
confidence: 99%
“…After successful kidney transplantation, ESRD patients subsequently have significant improvement in renal function resulting in urinary excretion of metabolites that increases risk of stone disease. Studies have identified kidney stones in allograft kidney as one of the serious problems in kidney transplant recipients[12-40]. However, unlike the general population, the incidence and characteristics of kidney stones in kidney transplant recipients are not well studied.…”
Section: Introductionmentioning
confidence: 99%
“…Genel olarak asemptomatik nakil böbrekteki 4 mm altındaki kalküller güvenle izlenebilir, bu taşlar spontan düşme eğilimindedir 12,13 . Literatürde böbrek nakli sonrası üriner sistem taşı ve obstrüksiyon nedeniyle nefrostomi kateteri takılan ve ESWL, URS ve PCNL gibi tedavi yöntemlerinin uygulandığı hastalar bildirilmiştir 10,14,15 . Geniş serilerde %80 üzeride başarı ile etkili ve güvenli şekilde uygulanabilen bir yöntem olan ESWL tedavisi böbrek nakli öncesi veya nakil sonrası taşlı allogrefte uygulanabilir.…”
Section: Olguunclassified
“…2 And also, the proximity to the bony pelvis causes that targeting the shock wave directly onto the stone becomes more difficult in ESWL. 1,4,9,10,22 But the anatomic position in the iliac fossa with the renal surface close to skin makes PCNL an attractive alternative and a feasible procedure in the treatment of urinary calculi. 10 Many cases have been reported in which allograft lithiass was treated successfully with PCNL.…”
Section: 391121mentioning
confidence: 99%
“…[1][2][3][4] Among them urinary stone is a rare complication and its prevalence reported between 0.2% and 6.3%. 1,2,[5][6][7][8] Urinary calculi are often asymptomatic so it is difficult to diagnose them at an early stage by physicians 1 and they are usually diagnosed when a sudden worsening kidney function happens or pyelonephritis is detected. 2 The best and most accurate method to detect the size and location of the stone is ultrasound.…”
Section: Introductionmentioning
confidence: 99%